Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Solid acid catalyzed synthesis of furans from carbohydrates - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Reviews-Science and Engineering, 2016)
The alternative feedstock, biomass (particularly lignocelluloses), having the profuse availability, is promising for the synthesis of several value-added chemicals which are currently obtained from fossil feedstock. In this article, the synthesis of two extremely significant furan chemicals viz. furfural and 5-hydroxymethylfurfural (HMF) are discussed. In the synthesis of furans from biomass, numerous challenges, i.e., use of edible sugars as substrates, selectivity to furans, their isolation in pure form, reuse of catalyst, environmental issues, etc., are perceived and in the recent past researchers tried to resolve those by developing advance methodologies. This article comprehensively summarizes the latest progress made in the above-mentioned areas and also provides commentary on the analyses of results, rationale for observed activity and mechanisms, etc. It also discusses future aspects of this work.
Keywords: Biomass conversion; carbohydrates; cellulose; furans; furfural; hemicelluloses; HMF; solid acid catalyst

TiO2-based water-tolerant acid catalysis for biomass-based fuels and chemicals - Sudarsanam, Putla; Li, Hu; Sagar, Tatiparthi Vikram (ACS Catalysis, 2020)
Solid acid catalysts alone or in combination with redox metals play a pivotal role in biomass valorization to obtain alternative fuels and chemicals. In acid-catalyzed biomass conversions, water is a key reagent/byproduct that can induce leaching/poisoning of catalyst's acid species, a major problem toward catalyst recyclability and product purification. Thus, developing efficient water-tolerant solid acid catalysts is vital for viable biomass valorization. TiO2 is considered to be a promising water-tolerant solid acid catalyst for biomass conversions because of the presence of coordinatively unsaturated Ti4+ sites, which are robust and less prone to leaching in the aqueous medium. Besides, the synergistic combination of TiO2 with redox metals (Ru, Pd, Ni, Cu, etc.) provides abundant bifunctional acid-redox sites, which exhibit a favorable catalytic role in the deoxygenation of biomass molecules to practically useful hydrocarbons. Therefore, this review provides an overview of recent progress toward TiO2-based water-tolerant acid catalysis for biomass conversion, with a focus on hydrothermal stability of TiO2, its acidity, and catalysts' synthesis methods. Various biomass conversions over TiO2-based catalysts, where water-tolerant acid sites or acid-redox dual sites show a significant catalytic effect, were discussed. Structure-activity relationships based on water-tolerant Lewis acidity of TiO2 were emphasized. We believe that this review will provide valuable information for developing efficient water-tolerant solid acid catalysts not only for biomass valorization but also for other challenging reactions in the aqueous medium.
Keywords: Acid catalysis; acid-redox catalysis; Biomass conversion; renewable fuels and chemicals; TiO2-based catalysts; water-tolerant Lewis acidity

Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts

Promoting effect of titanium on C-O hydrogenolysis of erythritol to 1,4-butanediol over Pt/W/Ti-SBA-15 catalysts - Bhowmik, Susmita; Akula, Venugopal; Sethia, Govind; Marimuthu, Banu; Darbha, Srinivas (Applied Catalysis A-General, 2023)
The C-O hydrogenolysis of erythritol was investigated using Pt/W/Ti-SBA-15 catalysts (4 wt% Pt, 1 wt% W and Si/Ti molar ratio = 50, 33, 20 and 10). Ti-incorporation enhanced the hydrogenolysis activity and the yield of 1,4-butanediol (1,4-BDO). A catalyst with Si/Ti = 20 afforded erythritol conversion of 94 mol% with 1,4-BDO yield of 32.6 mol% and total BDOs yield of 51.7 mol% at 190 degrees C, 50 bar H2 and 12 h. For the catalyst with no titanium (Pt/W/SBA-15), a double the time was required to achieve such yield. There observed electronic connectivity amongst Ti, Pt and W. For the catalyst with Si/Ti = 20, a greater amount of interfacial Pt-O-W(Ti) sites with Pt in + 2 oxidation state was present. The enhanced catalytic performance of these catalysts was corresponded to dispersed Pt (that facilitate hydrogen activation and spillover) and acidic interfacial Pt-O-W sites (that promote the adsorption and hydrogenolysis of erythritol to diols).
Keywords: Biomass conversion; Erythritol; Hydrogenolysis; Polyols; Promotional effect of Ti; Terminal diol; Ti-SBA-15-supported Pt/W catalysts

Selective and robust Ru catalyst for the aqueous phase aerobic oxidation of furfural to 2-furoic acid - Lokhande, Priya; Dhepe, Paresh L. (ACS Applied Materials & Interfaces, 2023)
Synthesis of 2-furoic acid (FURA) via oxidation of furfural (FAL) is vital in evolving the biorefinery concept as FURA has numerous important applications in the pharmaceuticals and optic areas. Though few works on this reaction are done, those are marred with shortcomings such as the nonrecyclability of catalyst, dilute solutions, lower yields, or use of H2O2 as an oxidizing agent. Herein, we report catalytic aqueous phase oxidation of FAL to FURA using molecular oxygen as an oxidizing agent. For the synthesis of FURA, various catalysts with a combination of metal (Pt, Pd, Ru) and supports (carbon, Al2O3) were prepared and characterized by multiple techniques (X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS)). Oxidation of FAL carried out over 5 wt % Ru/C catalyst in the presence of Na2CO3 yielded 83% of FURA at 120 degrees C and 15 bar oxygen pressure. The catalyst could show potential for reusability as similar activity was achieved after subjecting the spent catalyst to mild reduction treatment (150 degrees C). Studies on the effects of temperature, pressure, and time could help accomplish enhanced yields of FURA. Additionally, learning about the effect of base (weak/strong/solid) revealed that due to the weak basicity of Na2CO3, higher yields could be achieved by maintaining approximately a pH of 11, which is optimal for suppressing side reactions. Under the given conditions, FURA is stable (>90%) and also adsorption studies divulge that it is immediately removed from the catalyst surface, and hence higher yields could be achieved in our catalytic system. Using the initial rates methodology, an activation energy of 21.91 kJ mol(-1) was derived and also a high turn over frequency (TOF) (85.9 h(-1)) was observed under optimized conditions.
Keywords: 2-furoic acid (FURA); Biomass conversion; furfural (FAL); heterogeneous catalyst; Oxidation; ruthenium on carbon etc

Selective hydrogenation of furfural to furfuryl alcohol over Pd supported on ternary oxide in aqueous medium under mild conditions - Nehra, Pooja; Betsy, K. J.; Vinod, C. P. (ChemCatChem, 2025)
We report palladium (Pd) supported on a mixed CuO/ZnO/Al2O3 catalyst for the synthesis of furfuryl alcohol (FA) from furfural (FF) using hydrogen under near atmospheric pressure (balloon pressure) conditions. A systematic study of various metal oxide combinations revealed that the best support for Pd nanoparticles is a CuO/ZnO/Al2O3 mixed system, which results in excellent catalytic performance. A series of control experiments highlighted the essential role of mixed Cu-Zn-Al oxide support in facilitating the adsorption and activation of FF. Our results demonstrate that under optimal conditions (40 degrees C, balloon pressure H2), the catalyst yields FF conversion exceeding 98%, with remarkable selectivity for FA reaching up to 99% with water as solvent. The catalyst exhibited almost comparable activity up to three catalytic cycles without extra catalyst treatment or reactivation with negligible Pd leaching. These findings shed insight into the design of mixed metal oxide-based support for active metal interactions in optimizing catalytic performance in furfural hydrogenation under mild conditions.
Keywords: Biomass conversion; Furfural hydrogenation; Furfuryl alcohol; mixed metal oxides; Pd catalyst

Towards efficient conversion of sucrose to 1,2-propanediol selectively over Cu-La on activated carbon support - Anilan, Anusree Elavanaparambil; Sreekantan, Sreejith; Racha, Arundhathi; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2025)
In this study, we investigated the conversion of sucrose to 1,2-propanediol (1,2-PDO) using various Cu-La metals supported on activated carbon (AC), a versatile support known for its hydrophobicity and high surface area. Among the catalysts tested, 6% Cu-20% La/AC demonstrated the highest activity, achieving a 72% yield of 1,2-PDO under optimal reaction conditions of 200 degrees C, 40 bar H2, and 6-h reaction time. Comparative studies using cellulose, sucrose, glucose, and fructose as substrates identified sucrose as the most favorable feedstock for 1,2-PDO production. Detailed catalyst characterization (XRD, TEM, FE-SEM, TPR, TPD, XPS) revealed that the high dispersion, presence of metallic copper, and synergy between Cu and La, along with the presence of optimal acidic and basic sites, were responsible for the catalyst's high selectivity of 1,2-PDO. Additionally, the effect of different supports, including HY, NaY, HZSM-5, NaZSM-5, gamma-Al2O3, and AC, on sucrose conversion was examined, with AC showing superior performance. The catalyst's reusability was also assessed.Graphical abstractInvestigation of Cu-La metals supported on activated carbon for the catalytic conversion of sucrose to 1,2-propanediol, with an emphasis on choice of support, feedstock selection, catalyst performance, and stability under optimized reaction conditions.
Keywords: 1; 2-Propanediol; Biomass conversion; Biomass-to-chemicals; Hydrogenation